2022
DOI: 10.1007/s00204-022-03395-y
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cytochrome P450 enhances the nephro- and hepatotoxicity of ochratoxin A

Abstract: The mycotoxin ochratoxin A (OTA) is a contaminant in food that causes nephrotoxicity and to a minor degree hepatotoxicity. Recently, we observed that OTA induces liver damage preferentially to the cytochrome P450 (CYP)-expressing pericentral lobular zone, similar to hepatotoxic substances known to be metabolically toxified by CYP, such as acetaminophen or carbon tetrachloride. To investigate whether CYP influences OTA toxicity, we used a single dose of OTA (7.5 mg/kg; intravenous) with and without pre-treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“…The residue of OTA in the body is mainly closely related to its biological transformation and transportation . AHR and its ligands AHRNT and PXR are the main enzymes responsible for metabolizing OTA, and AHR can activate downstream CYP1A and CYP3A enzymes .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The residue of OTA in the body is mainly closely related to its biological transformation and transportation . AHR and its ligands AHRNT and PXR are the main enzymes responsible for metabolizing OTA, and AHR can activate downstream CYP1A and CYP3A enzymes .…”
Section: Discussionsupporting
confidence: 93%
“…The residue of OTA in the body is mainly closely related to its biological transformation and transportation. 45 AHR and its ligands AHRNT and PXR are the main enzymes responsible for metabolizing OTA, and AHR can activate downstream CYP1A and CYP3A enzymes. 45 Our results showed that as the OTA dose increased, the AHR, AHRNT, PXR, CYP1A, and CYP3A mRNA expressions significantly increased.…”
Section: Ota Affected Metabolism and Residue In Grassmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in in vitro studies, these markers were not so suitable for the detection the nephrotoxic effects of OTA (Rached et al, 2008). On the contrary, OTA treatment was applied to mice where KIM-1 and NGAL were used to monitor the nephrotoxicity of the xenobiotics (Hassan et al, 2022). Studies have also been carried out using serum or blood samples collected to determine biochemical parameters which reflect kidney function (Mohd Redzwan et al, 2014).…”
Section: Kidney Biomarkers In Detecting Mycotoxin Induced Nephrotoxicitymentioning
confidence: 99%
“…Ochratoxins are a group of mycotoxins produced by Aspergillus species, e.g., Aspergillus niger as well as some Penicillium which can exert damage to organisms (Ringot et al, 2006). For example, OTA disrupts several cell functions, including cell proliferation, division, and signaling pathways (Vettorazzi et al, 2013;Hassan et al, 2022), it also has a synergistic effect on other co-occurring mycotoxins (Liu et al, 2022a).…”
Section: Mycotoxin Exposure and General Introduction Of Nephrotoxic M...mentioning
confidence: 99%